HLWM-info. - Homo- en lesbiennewerking Mechelen (HLWM) (Mechelen : HLWM, 1987)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie: Adegemstraat 55, 2800 Mechelen ; vanaf (1992) 5 : Hanswijkstraat 74, 2800 Mechelen
Nederlands
Periodiek